2008
DOI: 10.1111/j.1530-0277.2008.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Response to Emotional Stress: An Assessment Across Subjective, Behavioral, and Physiological Domains and Relations to Alcohol Craving

Abstract: Background-Women and men are at risk for different types of stress-related disorders, with women at greater risk for depression and anxiety and men at greater risk for alcohol-use disorders. The present study examines gender differences in emotional and alcohol craving responses to stress that may relate to this gender divergence in disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
169
3
15

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(213 citation statements)
references
References 57 publications
26
169
3
15
Order By: Relevance
“…The finding that women had greater negative emotional response to the stress paradigm is consistent with Chaplin et al (2008) results with heavy social drinkers. However, this study differs from Chaplin in that the women in the present study exhibited greater craving than the men.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The finding that women had greater negative emotional response to the stress paradigm is consistent with Chaplin et al (2008) results with heavy social drinkers. However, this study differs from Chaplin in that the women in the present study exhibited greater craving than the men.…”
Section: Discussionsupporting
confidence: 80%
“…A human laboratory study of healthy social drinkers using guided imagery for stress induction found that women showed greater negative emotional response than men and that men's alcohol craving was associated with higher subjective emotional responses (Chaplin, Hong, Bergquist, & Sinha, 2008). The aforementioned study, however, Addictive Behaviors 38 (2013) 2643-2646 showed no sex differences in alcohol craving.…”
Section: Introductionmentioning
confidence: 57%
“…Regarding gender, a research carried out for the validation of the Brazilian version of PAID (16) showed that women had higher scores of stress related to emotional problems, corroborating the findings of this study and of the literature, showing that women present higher emotional distress (16,19,21) . With regard to age and diagnosis time, research show that older patients with more time of diagnosis may perceive the disease on a less stressful way (16,19) .…”
Section: Discussionsupporting
confidence: 77%
“…However, the conditions that are necessary for these effects remain to be determined. Important variables that may well moderate the Go and Stop processes include addiction status and gender, both of which have been found to affect responses to stress and cues on other cognitive indices (Chaplin et al, 2008;Fox et al, 2009;Lawrence et al, 2009;Li et al, 2009;Nesic and Duka, 2006;Udo et al, 2009). In addition, the present subjects were active drinkers and may therefore differ from individuals who have undergone treatment.…”
Section: Stress and Alcohol Cues On Go-stop Responding M Zack Et Almentioning
confidence: 99%